Data on recreational activities, respondents’ values, land use preferences, protection level and biodiversity in nature-based tourism areas in Finland - Anne Tolvanen; Katja Kangas; Oili Tarvainen; Esa Huhta; Anne Jäkäläniemi; Marketta Kyttä; Ari Nikula; Vesa Nivala; Seija Tuulentie; Liisa Tyrväinen (Data in Brief, 2020)
We present the first dataset that can be used to associate peoples’ opinions with comprehensive biodiversity and cultural heritage values. The socio-ecological dataset includes 1) place-based information on peoples’ recreational activities, values expressed as pleasant and unpleasant sites, and negative preferences concerning land use in terms of tourism, nature protection and forestry, and 2) compiled information on scored biodiversity values and protection level of sites. The data are organized in 1ha grid cells. The data were compiled from a rural nature-based tourism area in two municipalities northern Finland. Peoples’ opinions were assessed using a public participation geographic information system (PPGIS) and the data were merged with spatial biodiversity data from the same area. The data are directly related to the article Tolvanen et al. [1]. Biodiversity data, also utilized in Tolvanen et al. 2020, were compiled from various sources and scoring was done in Kangas et al. [2]. References to individual respondents and spatial locations of markings were removed. The data are useful in evaluating the relationship between people's values and biodiversity.